Determinants of Management Earnings Forecasts: The Case of Global Shipping IPOs. (18th May 2017) - Drobetz, Wolfgang; Gounopoulos, Dimitrios; Merika, Anna; Merikas, Andreas
Abstract: Firms that go public on global stock markets are not obliged to disclose earnings forecasts in their prospectuses. We use this fact to examine the shipping industry, where most firms voluntarily issue earnings forecasts during the IPO process, thus providing unique, international‐level evidence. We find overall pessimistic forecasts of ship owners, primarily because of the industry's uncertain and volatile environment. High ship owner participation after going public is associated with less accurate earnings forecasts. Our results further indicate that financial leverage, a listing in an emerging stock market, and global market conditions are other main factors responsible for inaccurate earnings forecasts.